ISO 9001:2015 IMPLEMENTATION PLANNING IN NON-FORMAL EDUCATIONAL INSTITUTIONS IN THE FIELD OF PROGRAMMING IN INDONESIA - Hernawan, Yosep; Filianti, Filianti; Rasto, Rasto; Musafa, Musafa (PT. Altin Riset Publishing, 2024)
This study aims to develop an implementation plan for ISO 9001:2015 in non-formal educational institutions in the programming field in Indonesia. The approach used in this study is descriptive qualitative with data collection techniques used are observation, interviews, and documentation studies. The study results show that non-formal educational institutions in the programming field in Indonesia have several deficiencies in implementing ISO 9001:2015, such as the absence of adequate documents to support the quality management system implementation. Based on the results of this study, an ISO 9001:2015 implementation plan can be prepared which consists of three stages. First, the preparation stage includes understanding the ISO 9001:2015 standard, document preparation, and employee training. Second, the implementation phase provides for the implementation of a quality management system according to ISO 9001:2015 standards and the measurement of system performance. Third, the maintenance stage includes the evaluation of the quality management system that has been implemented and follow-up on the results of the evaluation. The results of this study are proof that the application of ISO 9001:2015 in non-formal educational institutions in the field of programming is very important. The application of the ISO 9001:2015 concept is very important and this can be done immediately, without having to wait for the certification process.